Given that ${{a}_{1}},{{a}_{2}},{{a}_{3}},......{{a}_{n}}$ form an arithmetic progression, find the following sum $S=\sum\limits_{i=1}^{n}{\dfrac{{{a}_{i}}{{a}_{i+1}}{{a}_{i+2}}}{{{a}_{i}}+{{a}_{i+2}}}}$
(A) $S=\dfrac{n}{2}\left[ a_{1}^{2}+{{a}_{1}}d\left( n \right)+\dfrac{\left( n-2 \right)\left( 2n+5 \right)}{6}{{d}^{2}} \right]$
(B) $S=\dfrac{n}{2}\left[ a_{1}^{2}+{{a}_{1}}d\left( n+1 \right)+\dfrac{\left( n-2 \right)\left( 2n+5 \right)}{6}{{d}^{2}} \right]$
(C) $S=\dfrac{n}{2}\left[ a_{1}^{2}+{{a}_{1}}d\left( n+1 \right)+\dfrac{\left( n-1 \right)\left( 2n+5 \right)}{6}{{d}^{2}} \right]$
(D) $S=\dfrac{n}{2}\left[ a_{1}^{3}+{{a}_{1}}d\left( n+1 \right)+\dfrac{\left( n-1 \right)\left( 2n+5 \right)}{6}{{d}^{2}} \right]$
Answer
Verified
455.1k+ views
Hint: For answering this question we will use the basic concept regarding the arithmetic progressions. When given ${{a}_{1}},{{a}_{2}},.............{{a}_{n}}$ forms arithmetic progression we can say that ${{a}_{i+1}}={{a}_{i}}+d$ and ${{a}_{n}}={{a}_{1}}+\left( n-1 \right)d$ where $d={{a}_{2}}-{{a}_{1}}$ and the sum of the $n$ term which is given as ${{S}_{n}}=\sum\limits_{i=1}^{n}{{{a}_{i}}}= \left( \dfrac{n}{2} \right)\left[ 2{{a}_{1}}+\left( n -1 \right)d \right]$
Complete step-by-step solution:
Now considering from the question we have been given that ${{a}_{1}},{{a}_{2}},.............{{a}_{n}}$ forms arithmetic progression. So we can say that ${{a}_{i+1}}={{a}_{i}}+d$ because ${{a}_{n}}={{a}_{1}}+\left( n-1 \right)d$ where $d={{a}_{2}}-{{a}_{1}}$ .
For answering this question we need to find the sum $S=\sum\limits_{i=1}^{n}{\dfrac{{{a}_{i}}{{a}_{i+1}}{{a}_{i+2}}}{{{a}_{i}}+{{a}_{i+2}}}}$
By substituting the respective values we will have,
$\begin{align}
& S=\sum\limits_{i=1}^{n}{\dfrac{{{a}_{i}}\left( {{a}_{i}}+d \right)\left( {{a}_{i}}+2d \right)}{{{a}_{i}}+{{a}_{i}}+2d}} \\
& \Rightarrow S=\sum\limits_{i=1}^{n}{\dfrac{{{a}_{i}}\left( {{a}_{i}}+d \right)\left( {{a}_{i}}+2d \right)}{2\left( {{a}_{i}}+d \right)}} \\
& \Rightarrow S=\dfrac{1}{2}\left[ \sum\limits_{i=1}^{n}{a_{i}^{2}+\sum\limits_{i=1}^{n}{2{{a}_{i}}d}} \right] \\
\end{align}$
Now, we will write the expansion of $\sum\limits_{i=1}^{n}{a_{i}^{2}}$
$\begin{align}
& \sum\limits_{i=1}^{n}{a_{i}^{2}}={{\sum\limits_{i=1}^{n}{\left( {{a}_{i}}+\left( i-1 \right)d \right)}}^{2}} \\
& \Rightarrow \sum\limits_{i=1}^{n}{\left( a_{i}^{2}+{{d}^{2}}{{\left( i-1 \right)}^{2}}+2{{a}_{i}}d\left( i-1 \right) \right)} \\
\end{align}$
By expanding the terms $\sum\limits_{i=1}^{n}{\left( i-1 \right)}$ and $\sum\limits_{i=1}^{n}{{{\left( i-1 \right)}^{2}}}$, we will get the below equation using $\sum\limits_{i=1}^{n}{i}=\dfrac{n\left( n-1 \right)}{2}$ and $\sum\limits_{i=1}^{n}{{{i}^{2}}}=\dfrac{n\left( n-1 \right)\left( 2n-1 \right)}{6}$ we will have $\sum\limits_{i=1}^{n}{a_{i}^{2}}=na_{i}^{2}+{{d}^{2}}\left( \dfrac{n\left( n-1 \right)\left( 2n-1 \right)}{6} \right)+2{{a}_{i}}d\left( \dfrac{n\left( n-1 \right)}{2} \right)$
We will also use the formulae for the sum of $n$ terms which is given as ${{S}_{n}}=\sum\limits_{i=1}^{n}{{{a}_{i}}}= \left( \dfrac{n}{2} \right)\left[ 2{{a}_{1}}+\left( n -1 \right)d \right] $
Now, by using this value, we will get the below equation. After substituting we will simplify the equation more further very carefully.
$\begin{align}
& S=\dfrac{1}{2}\left[ na_{1}^{2}+{{d}^{2}}\left( \dfrac{n\left( n-1 \right)\left( 2n-1 \right)}{6} \right)+2{{a}_{1}}d\left( \dfrac{n\left( n-1 \right)}{2} \right) \right]+2d\left( \dfrac{n}{2} \right)\left[ 2{{a}_{1}}+\left( n -1 \right)d \right] \\
& \Rightarrow S=\dfrac{1}{2}\left[ na_{1}^{2}+{{d}^{2}}\left( \dfrac{n\left( n -1 \right)\left( 2n-1 \right)}{6} \right)+2{{a}_{1}}d\left( \dfrac{n\left( n-1 \right)}{2} \right) \right]+2{{a}_{1}}dn+{{d}^{2}}n\left( n -1 \right) \\
& \Rightarrow S=\dfrac{1}{2}\left[ na_{1}^{2}+{{d}^{2}}n\left( n-1 \right)\left[ \dfrac{2n-1}{6}+1 \right]+2{{a}_{1}}dn\left[ \dfrac{n -1}{2}+1 \right] \right] \\
& \Rightarrow S=\dfrac{1}{2}\left[ na_{1}^{2}+\left( \dfrac{{{d}^{2}}n\left( n-1 \right)\left( 2n+5 \right)}{6} \right)+{{a}_{1}}dn\left( n+1 \right) \right] \\
& \Rightarrow S=\dfrac{n}{2}\left[ a_{1}^{2}+\left( \dfrac{{{d}^{2}}\left( n -1 \right)\left( 2n+5 \right)}{6} \right)+{{a}_{1}}d\left( n+1 \right) \right] \\
\end{align}$
Therefore option C is the correct option.
Note: While answering questions of this type we should be sure with the concept and expansions we make. Similar to arithmetic progression there exist geometric progression when given ${{a}_{1}},{{a}_{2}},.............{{a}_{n}}$ forms geometric progression we can say that ${{a}_{i+1}}={{a}_{i}}r$ and ${{a}_{n}}={{a}_{1}}{{r}^{n-1}}$ where $r=\dfrac{{{a}_{2}}}{{{a}_{1}}}$ and the sum of the $n$ term which is given as ${{S}_{n}}=\sum\limits_{i=1}^{n}{{{a}_{i}}}=\dfrac{{{a}_{1}}\left( {{r}^{n}}-1 \right)}{\left( r-1 \right)}$.
Complete step-by-step solution:
Now considering from the question we have been given that ${{a}_{1}},{{a}_{2}},.............{{a}_{n}}$ forms arithmetic progression. So we can say that ${{a}_{i+1}}={{a}_{i}}+d$ because ${{a}_{n}}={{a}_{1}}+\left( n-1 \right)d$ where $d={{a}_{2}}-{{a}_{1}}$ .
For answering this question we need to find the sum $S=\sum\limits_{i=1}^{n}{\dfrac{{{a}_{i}}{{a}_{i+1}}{{a}_{i+2}}}{{{a}_{i}}+{{a}_{i+2}}}}$
By substituting the respective values we will have,
$\begin{align}
& S=\sum\limits_{i=1}^{n}{\dfrac{{{a}_{i}}\left( {{a}_{i}}+d \right)\left( {{a}_{i}}+2d \right)}{{{a}_{i}}+{{a}_{i}}+2d}} \\
& \Rightarrow S=\sum\limits_{i=1}^{n}{\dfrac{{{a}_{i}}\left( {{a}_{i}}+d \right)\left( {{a}_{i}}+2d \right)}{2\left( {{a}_{i}}+d \right)}} \\
& \Rightarrow S=\dfrac{1}{2}\left[ \sum\limits_{i=1}^{n}{a_{i}^{2}+\sum\limits_{i=1}^{n}{2{{a}_{i}}d}} \right] \\
\end{align}$
Now, we will write the expansion of $\sum\limits_{i=1}^{n}{a_{i}^{2}}$
$\begin{align}
& \sum\limits_{i=1}^{n}{a_{i}^{2}}={{\sum\limits_{i=1}^{n}{\left( {{a}_{i}}+\left( i-1 \right)d \right)}}^{2}} \\
& \Rightarrow \sum\limits_{i=1}^{n}{\left( a_{i}^{2}+{{d}^{2}}{{\left( i-1 \right)}^{2}}+2{{a}_{i}}d\left( i-1 \right) \right)} \\
\end{align}$
By expanding the terms $\sum\limits_{i=1}^{n}{\left( i-1 \right)}$ and $\sum\limits_{i=1}^{n}{{{\left( i-1 \right)}^{2}}}$, we will get the below equation using $\sum\limits_{i=1}^{n}{i}=\dfrac{n\left( n-1 \right)}{2}$ and $\sum\limits_{i=1}^{n}{{{i}^{2}}}=\dfrac{n\left( n-1 \right)\left( 2n-1 \right)}{6}$ we will have $\sum\limits_{i=1}^{n}{a_{i}^{2}}=na_{i}^{2}+{{d}^{2}}\left( \dfrac{n\left( n-1 \right)\left( 2n-1 \right)}{6} \right)+2{{a}_{i}}d\left( \dfrac{n\left( n-1 \right)}{2} \right)$
We will also use the formulae for the sum of $n$ terms which is given as ${{S}_{n}}=\sum\limits_{i=1}^{n}{{{a}_{i}}}= \left( \dfrac{n}{2} \right)\left[ 2{{a}_{1}}+\left( n -1 \right)d \right] $
Now, by using this value, we will get the below equation. After substituting we will simplify the equation more further very carefully.
$\begin{align}
& S=\dfrac{1}{2}\left[ na_{1}^{2}+{{d}^{2}}\left( \dfrac{n\left( n-1 \right)\left( 2n-1 \right)}{6} \right)+2{{a}_{1}}d\left( \dfrac{n\left( n-1 \right)}{2} \right) \right]+2d\left( \dfrac{n}{2} \right)\left[ 2{{a}_{1}}+\left( n -1 \right)d \right] \\
& \Rightarrow S=\dfrac{1}{2}\left[ na_{1}^{2}+{{d}^{2}}\left( \dfrac{n\left( n -1 \right)\left( 2n-1 \right)}{6} \right)+2{{a}_{1}}d\left( \dfrac{n\left( n-1 \right)}{2} \right) \right]+2{{a}_{1}}dn+{{d}^{2}}n\left( n -1 \right) \\
& \Rightarrow S=\dfrac{1}{2}\left[ na_{1}^{2}+{{d}^{2}}n\left( n-1 \right)\left[ \dfrac{2n-1}{6}+1 \right]+2{{a}_{1}}dn\left[ \dfrac{n -1}{2}+1 \right] \right] \\
& \Rightarrow S=\dfrac{1}{2}\left[ na_{1}^{2}+\left( \dfrac{{{d}^{2}}n\left( n-1 \right)\left( 2n+5 \right)}{6} \right)+{{a}_{1}}dn\left( n+1 \right) \right] \\
& \Rightarrow S=\dfrac{n}{2}\left[ a_{1}^{2}+\left( \dfrac{{{d}^{2}}\left( n -1 \right)\left( 2n+5 \right)}{6} \right)+{{a}_{1}}d\left( n+1 \right) \right] \\
\end{align}$
Therefore option C is the correct option.
Note: While answering questions of this type we should be sure with the concept and expansions we make. Similar to arithmetic progression there exist geometric progression when given ${{a}_{1}},{{a}_{2}},.............{{a}_{n}}$ forms geometric progression we can say that ${{a}_{i+1}}={{a}_{i}}r$ and ${{a}_{n}}={{a}_{1}}{{r}^{n-1}}$ where $r=\dfrac{{{a}_{2}}}{{{a}_{1}}}$ and the sum of the $n$ term which is given as ${{S}_{n}}=\sum\limits_{i=1}^{n}{{{a}_{i}}}=\dfrac{{{a}_{1}}\left( {{r}^{n}}-1 \right)}{\left( r-1 \right)}$.
Recently Updated Pages
Master Class 11 Accountancy: Engaging Questions & Answers for Success
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Trending doubts
Define least count of vernier callipers How do you class 11 physics CBSE
The combining capacity of an element is known as i class 11 chemistry CBSE
Proton was discovered by A Thomson B Rutherford C Chadwick class 11 chemistry CBSE
Find the image of the point 38 about the line x+3y class 11 maths CBSE
Can anyone list 10 advantages and disadvantages of friction
Distinguish between Mitosis and Meiosis class 11 biology CBSE